Notes to Philosophy 167: Class 1 -- Overview of the Course;Ptolemaic Astronomy -- Part 14. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: The Achievement of Ptolemaic Astronomy -- Shortcomings of Ptolemaic Astronomy -- Introduction: Ptolemy as Bad Science? -- Issue: What Claim is Ptolemaic Theory Making? -- Issue: Is It Bad Because It Is Too Complicated? -- Issue: Is It Bad Because It Is Simply False? -- Issue: Is It Bad Because It Is Too Inaccurate? -- Select Sources.; Generally corresponds to the video segment: Class 1, Part 14.